Systemic Factors Influencing Student Performance in Accounting Education: A South African Perspective - Makhathini, LR; Isabirye, AK (Journal of Ecohumanism, 2025)
This study investigated the systemic factors influencing student achievement in accounting education, with a particular focus on pedagogical practices, institutional support, socio-economic factors, and counseling and guidance services. Utilizing qualitative data collection methodologies, the research engaged ten participants, comprising five students (code-named S1 to S5) and five lecturers (code-named T1 to T5), to gain a comprehensive understanding of their experiences and insights. Data analysis revealed four primary themes that significantly impact student performance. The findings indicated that effective pedagogical practices and robust institutional support play crucial roles in enhancing student outcomes, while socio-economic disparities often create barriers to academic success. Additionally, the study highlighted the vital importance of adequate counseling and guidance services in facilitating student navigation through their educational journey. Based on these results, the study recommends that educational institutions implement targeted training for instructors on inclusive teaching approaches, enhance support mechanisms such as academic advising and financial aid, and invest in comprehensive counseling services. Future research should focus on longitudinal studies examining the effects of these interventions on student performance, as well as exploring the experiences of students from diverse socio-economic backgrounds across various educational settings. By addressing these systemic barriers, the aim is to create a more equitable and supportive learning environment for students in accounting education.